Antenatal counselling- is it adequate? A cross-sectional study from Chandigarh tricity, India - Dhiman, Anupama; Goel, Naveen K.; Kumar, Dinesh; ., Navpreet; Galhotra, Abhiruchi (International Journal Of Community Medicine And Public Health, 2017)
Background: Antenatal care (ANC) provides an important opportunity to improve maternal understanding about pregnancy, childbirth, and care of the newborn. Adequate and quality ANC can help ensure a favourable pregnancy outcome, but the coverage of ANC in India remains inadequate. The present study was conducted with an objective to assess ante natal counselling services at health centers in Chandigarh Tricity. Methods: The cross-sectional study was conducted in the Chandigarh Tricity during April 2012 to September 2013. Stratified multistage sampling technique was used to select health centers in tricity. A total of 345 pregnant women in second and third Trimester were interviewed with the help of pre-designed, structured and pre-tested questionnaire after taking their written informed consent. It was supplemented by observation of ante natal sessions. Data was entered and analyzed using SPSS version 19. Results: Nearly one-fourth (28.1%) participants received counselling regarding diet and rest. Only 26 (07.5%) participants were explained about danger signs during pregnancy. Significant difference was found between counseling given regarding ‘diet and rest’ with respect to city (p=0.03) and health centers (p=0.00). Significant difference was found between counselling for ‘family planning’ with respect to city (p=0.01) and health centers (p=0.00). Conclusions: Findings from our study indicate low level of counselling on various components of ANC. Thus, strategies under National Health Mission to improve quality of antenatal communication as well as maternal understanding should be strengthened.